Nigeria Policemen Digital Memes as Reformative Indices - Oluremi, Tolulope Abisodun; Olaniyana, Oluwayomi Rosemary (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
The corrupt activities of some officers of the Nigeria Police Force (NPF) at checkpoints have in recent times drawn the senses of hypermemetic logic. A number of research studies have investigated Nigerian police discourse. However, digital memes deployed to reflect corruption-related activities at police checkpoints have attracted inconsequential research. This paper, therefore, examines selected Nigeria Police digital memes – multi-moulded socially constructed Nigeria police discourse, instantiated digitally to satirise corruptible policing and privilege reformative advocacy in Nigeria. Seven selected police digital memes were collected from Opera News Nigeria, an app that allows African authors and bloggers to create online content and share such with a fast-growing subscriber base. In interpreting the selected digital police memes, this paper engages the theoretical underpinnings of Gunther Kress’ (2010) social-semiotic theory of multimodality. Through its theoretical apparatus, functional loads such as contemptible open extortion, symbolic blind allusions, duty deviance, wrong motif towards checkpoints, detrimental frustration, checkpoints’ main duty negligence and lawlessness were established. Thus, this paper concludes that the satirical philosophy embedded within most Nigeria Police digital memes points towards reformation and reorientation of members of the Nigeria Police Force.